Effect of hypoxia on the proliferation of porcine bone marrow-derived mesenchymal stem cells and adipose-derived mesenchymal stem cells in 2- and 3-dimensional culture. Issue 3 (March 2017) - Burian, Egon; Probst, Florian; Palla, Benjamin; Riedel, Christina; Saller, Maximilian Michael; Cornelsen, Matthias; König, Florian; Schieker, Matthias; Otto, Sven
Abstract: Objective: Bone marrow-derived mesenchymal stem cells (MSCs) and adipose-derived mesenchymal stem cells (ASCs) currently represent a promising tool for the regeneration of large bony defects. Therefore, it is pivotal to find the best cell source within the body and the best conditions for in vitro cellular expansion. This study compared cellular response of MSCs and ASCs from a porcine animal in normoxic (21% O2) and hypoxic (2% O2) cell culture conditions via 2D and 3D experimental settings. Materials and methods: The effect of constant exposure to hypoxia on primary pig stem cells was evaluated by two methods. First, a cumulative population doublings (cumPD) over a period of 40 days, a metabolic activity assay in both 2D and 3D beta-TCP-PHB scaffolds, followed by analysis of osteogenic differentiation potential in cell monolayers. Results: Our results displayed enhanced cell culture proliferation in 2% O2 for both MSCs and ASCs, with impaired osteogenic differentiation of MSCs. The impact of constant hypoxia on porcine MSCs and ASCs exhibited a statistically significant decrease in osteogenic differentiation under hypoxic conditions with the MSCs. Conclusions: Our data suggest that MSCs and ASCs expanded in hypoxic culture conditions, might be more suitable for use in the clinical setting where large cell numbers are required. When differentiated in normoxic conditions, MSCs showed the highest osteogenic differentiation potential and might be the best choice of cells with consideration to bone repair.